Pterosin sesquiterpenoids from Pteris laeta Wall. ex Ettingsh. protect cells from glutamate excitotoxicity by modulating mitochondrial signals. (23rd May 2023) - Cheng, Aifang; Zhang, Yan; Sun, Jin; Huang, Duli; Sulaiman, Jordy Evan; Huang, Xin; Wu, Long; Ye, Wenkang; Wu, Chuanhai; Lam, Henry; Shi, Yusheng; Qian, Pei-Yuan
Abstract: Ethnopharmacological relevance: The genus Pteris (Pteridaceae) has been used as a traditional herb for a long time. In particular, Pteris laeta Wall. ex Ettingsh. has been widely used in traditional Chinese medicine to treat nervous system diseases and some pterosin sesquiterpenes from Pteris show neuroprotective activity, but their underlying molecular mechanisms remain elusive. Therefore, to investigate the neuroprotective activity and working mechanism of pterosin sesquiterpenes from P. laeta Wall. ex Ettingsh. will provide a better understanding and guidance in using P. laeta Wall. ex Ettingsh. as a traditional Chinese medicine. Aim of the study: We aim to develop effective treatments for neurodegenerative diseases from pterosin sesquiterpenes by evaluating their neuroprotective activity and investigating their working mechanisms. Materials and methods: Primary screening on the glutamate-induced excitotoxicity cell model was assessed by 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-Diphenyltetrazolium Bromide (MTT) assay. Fluorescent-activated cell sorting (FACS) was used to analyze the activation level of glutamate receptors and mitochondria membrane potential after treatment. Transcriptomics and proteomics analysis was performed to identify possible targets of pterosin B. The key pathways were enriched by the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis through the Database for Annotation, Visualization, and Integrated Discovery (DAVID). The core targets were visualized by a protein-protein interaction network using STRING. The mRNA and protein expressions were evaluated using real-time quantitative polymerase chain reaction (Q-PCR) and western blot, respectively. Immunocytochemistry was performed to monitor mitochondrial and apoptotic proteins. Cellular reactive oxygen species (ROS) were measured by ROS assay, and Ca 2+ was stained with Fluo-4 AM to quantify intracellular Ca 2+ levels. Results: We found pterosin B from Pteris laeta Wall. ex Ettingsh. showed significant neuroprotective activity against glutamate excitotoxicity, enhancing cell viability from 43.8% to 105% ( p -value: <0.0001). We demonstrated that pterosin B worked on the downstream signaling pathways of glutamate excitotoxicity rather than directly blocking the activation of glutamate receptors. Pterosin B restored mitochondria membrane potentials, alleviated intracellular calcium overload from 107.4% to 95.47% ( p -value: 0.0006), eliminated cellular ROS by 36.55% ( p -value: 0.0143), and partially secured cells from LPS-induced inflammation by increasing cell survival from 46.75% to 58.5% ( p -value: 0.0114). Notably, pterosin B enhanced the expression of nuclear factor-erythroid factor 2-related factor 2 (NRF2) and heme oxygenase-1 (HO-1) by 2.86-fold ( p -value: 0.0006) and 4.24-fold ( p -value: 0.0012), and down-regulated Kelch-like ECH-associated protein 1 (KEAP1) expression by 2.5-fold ( p -value: 0.0107), indicating that it possibly promotes mitochondrial biogenesis and mitophagy to maintain mitochondria quality control and homeostasis, and ultimately inhibits apoptotic cell death. Conclusions: Our work revealed that pterosin B protected cells from glutamate excitotoxicity by targeting the downstream mitochondrial signals, making it a valuable candidate for developing potential therapeutic agents in treating neurodegenerative diseases. Graphical abstract: Image 1 Highlights: Pterosin B from Pteris laeta Wall. ex Ettingsh. could protect cells from glutamate excitotoxicity. Pterosin B targets the downstream signaling pathways rather than directly blocking the activation of glutamate receptors. The mode of action of pterosin B is probably via targeting mitochondria by modulating the NRF2/HO-1 signaling pathway. Pterosin B could be a valuable candidate for developing potential therapeutic agents targeting neurodegenerative diseases.